Coping Stress Remaja Akibat Perceraian Orang Tua Di Dusun X, Kabupaten Lamongan - Andhika Rayhan Savero; Vira Ardella Yushillia (CV. ITTC INDONESIA, 2025)
This study aims to understand stress coping patterns in adolescents who are victims of parental divorce in Hamlet X, Lamongan Regency. The research used a qualitative method with a case study approach, involving one 19-year-old subject selected based on purposive sampling technique. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results showed that the subject experienced stress due to poor economic conditions, family conflict, and verbal abuse. The impact of stress includes changes in character to become more aggressive, lazy learning behavior, and the decision to drop out of college. Subjects adopted various coping strategies, such as escapism (avoiding the problem), seeking instrumental social support (seeking social support), self-blame (blaming oneself), and minimization (ignoring the problem). This study highlights the importance of social support and effective stress management to help adolescents deal with the psychological impact of parental divorce. This research is expected to be a reference in efforts to support the psychological well-being of adolescent victims of divorce and provide insight for the community in understanding the importance of family harmony.